PENGARUH WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA - Winanto Nawarcono Nawarcono; Agus Setiono (Kajian Ekonomi dan Bisnis, 2021)
Working is the main goal of someone in achieving self-actualization of their potential. Life in the workplace, work and family, work and personal fulfillment, work and social life, all illustrate the problem of a harmonious and balanced arrangement between work and other lives. In addition, the balance of employees at work and living quality of life is also the focus of company attention that will make employees more satisfied in carrying out each work. The company realizes the success of employees in working through achieving targets with exceptional performance, not solely because of the skills and competencies that employees have, but equally important is the balance of the employee in managing his personal quality of life with work demands. This research is a quantitative descriptive study. To measure the effect of Work-life Balance on Job Satisfaction, multiple linear regression methods are used with 55 respondents. The results of research that have been carried out that the variables in this study consisted of PLIW and WIPL which were stated to have a significant effect, as well as PLEW and WEPL which were stated to have no significant effect 91,4% of the Job Satisfaction of English Jogja Homes. Keywords: Self-actualization, Work-life Balance, Job Satisfaction.